Cell death in cells overlying lateral root primordia facilitates organ growth in Arabidopsis - Escamez, Sacha; Berthet, Béatrice; Maizel, Alexis (Current biology, 2020)
Plant organ growth is widely accepted to be determined by cell division and cell expansion, but, unlike that in animals, the contribution of cell elimination has rarely been recognized. We investigated this paradigm during Arabidopsis lateral root formation, when the lateral root primordia (LRP) must traverse three overlying cell layers within the parent root. A subset of LRP-overlying cells displayed the induction of marker genes for cell types undergoing developmental cell death, and their cell death was detected by electron, confocal, and light sheet microscopy techniques. LRP growth was delayed in cell-death-deficient mutants lacking the positive cell death regulator ORESARA1/ANAC092 (ORE1). LRP growth was restored in ore1-2 knockout plants by genetically inducing cell elimination in cells overlying the LRP or by physically killing LRP-overlying cells by ablation with optical tweezers. Our results support that, in addition to previously discovered mechanisms, cell elimination contributes to regulating lateral root emergence.
Gesehen am 04.03.2020